Best practice partnering in social housing development - Jones, Martyn (Thomas Telford, 2003)
This essential book provides a seven-step model for developing new supply chain relationships and how best to approach and manage sustainable partnerships. It identifies a number of benefits and dangers that can flow from close, open and more collaborative customer-supplier relationships.